1965
DOI: 10.1149/1.2423459
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Effects of Chloride and Sulfate Ions on Oxide Covered Aluminum

Abstract: The distribution of a-c resistance throughout the thickness of oxide film on aluminum specimens, conditioned by pre-exposure to 1.0N solutions of sodium chloride and sulfate, has been determined by an electrical method. This method involves measurement of series capacitance and dielectric loss of the oxide covered aluminum as the surface films thin slowly in a slightly alkaline, passivating, sodium chromate solution. Results show that chloride ions become included at certain selected locations in the oxide fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 9 publications
3
52
1
Order By: Relevance
“…As for carbonation-induced corrosion, there still is a lack in the physical understanding of the depassivation mechanism of steel exposed to chloride ions [92,187]. Two models are generally proposed: the ion exchange model [189] and the point defect model [190]. In the first one, depassivation is the result of the adsorption and ingress of Clthrough the outer film layer and the progressive thinning of the inner film until dissolution.…”
Section: Depassivation and Corrosion Mechanismsmentioning
confidence: 99%
“…As for carbonation-induced corrosion, there still is a lack in the physical understanding of the depassivation mechanism of steel exposed to chloride ions [92,187]. Two models are generally proposed: the ion exchange model [189] and the point defect model [190]. In the first one, depassivation is the result of the adsorption and ingress of Clthrough the outer film layer and the progressive thinning of the inner film until dissolution.…”
Section: Depassivation and Corrosion Mechanismsmentioning
confidence: 99%
“…The adsorption and penetration of Cl − on the passive film surface were achieved by means of oxygen vacancies. Heine et al [62] proposed the iron exchange model, which suggested that the ion penetration of oxide films was capable through an ion exchange process or through cation vacancies. The oxide layers on the metal surface contain defects and are porous in nature; thus, through these pores, aggressive ions can directly reach the metal/film interface to disturb passivity [63].…”
Section: Penetration and Film Breakdown Mechanismmentioning
confidence: 99%
“…In these models, the penetrated chlorides cause the dissolution of the passive film from within and/or increase the iron oxidation rate of the metal substrate such that the passive film breaks down due to excessive generation of oxides. Among these models, the ion exchange model 21 suggests a penetration of chloride ions into the oxide film through an ion exchange process (e.g., Cl − for lattice O 2− ). On the other hand, the pore models 22,23 are based on the fact that typical oxide layers contain flaws and are porous in nature; therefore, chlorides can pass through the pores and reach metal/film interface to disturb passivity.…”
Section: Depassivation Mechanismmentioning
confidence: 99%
“…Some of the depassivation models suggest that chlorides penetrate into the passive film through ion exchange processes or simple diffusion. [21][22][23] However, other models hypothesize that chlorides only act as a catalyst, without penetrating into the film, to form iron vacancies that eventually diffuse to the metal/film interface to initiate the depassivation process. 24,25 The debate between these different models is ongoing.…”
Section: Introductionmentioning
confidence: 99%